2021
DOI: 10.1002/pbc.29251
|View full text |Cite
|
Sign up to set email alerts
|

Exploring illness identity among children and youth living with cancer: A narrative review

Abstract: Background Children and youth with cancer may find it challenging to integrate illness into their pre‐existing identity—a phenomenon known as illness identity. In this critical narrative review, we explored illness identity among children and youth with cancer. Methods Three academic databases were searched. Twenty‐two articles were included in this review and each underwent thematic analysis. Results Cancer has both positive and negative influences on the identities of children and youth. Illness identity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…A narrative review of the illness identity among children and youth with cancer revealed that their experience profoundly affected their identity formation both positively and negatively. 23 The reliable relationships with health professionals observed repeatedly in our study could be a positive influence on children's identity formation. Similarly, a qualitative study on adolescents and young adults with cancer found that self-care or self-advocacy is essential for facing long-term illnesses.…”
Section: Inclusive Theme Illustrative Narrativesupporting
confidence: 54%
“…A narrative review of the illness identity among children and youth with cancer revealed that their experience profoundly affected their identity formation both positively and negatively. 23 The reliable relationships with health professionals observed repeatedly in our study could be a positive influence on children's identity formation. Similarly, a qualitative study on adolescents and young adults with cancer found that self-care or self-advocacy is essential for facing long-term illnesses.…”
Section: Inclusive Theme Illustrative Narrativesupporting
confidence: 54%
“…Illness identity as being gives an answer to the question ‘Who am I with regard to illness?’ (Posa et al., 2021, p. 1) and focuses on a person’s sense or understanding of themselves as ill (or not). Potential answers to that question vary from broad descriptions that are not further conceptualised to more elaborate responses.…”
Section: Resultsmentioning
confidence: 99%
“…Illness identity as being describes a constructed identity that is predominantly addressed in terms of change resulting from something new or additional, which, for example, is being internalised (e.g. Korsbek, 2013; Shostak & Fox, 2012), integrated (Posa et al., 2021) or replaced (Helgeson & Zajdel, 2017), but may also be addressed as, for example, developed (Ottewell, 2021) or created (Talbot et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More research and psychosocial support are needed to help young people with cancer navigate identity experiences and affective states during the cancer journey. HEART Lab student Stephanie Posa (2021) has recently completed a published review of literature on young people with cancer and identity. Indeed, the identity effects of cancer are complex and characterized by much fluidity and nuance.…”
Section: Chapter 5: Discussion and Future Directions Introductionmentioning
confidence: 99%